TINJAUAN KEBUTUHAN DAN DISTRIBUSI AIR BERSIH DI AIR BESAR (ARBES) DESA BATU MERAH - Natsir, Annisa Artika Diva; Lilipory, Isak; Hutubessy, Vector R. R (Journal Agregate, 2024)
Clean water is a source of life for every living creature, including humans who need drinking water and daily necessities. The aim of this final assignment is to determine the need for clean water for the community in Batu Merah Village, RT 004/ RW 017. Furthermore, to determine the capacity of water needs for the community at this time to find out the predicted increase in the population of RT 004 / RW 017 Air Besar Batu Merah Village and how much The RAB is large for community needs for the next 5 years (2023-2027). The data analysis technique used in this writing is a quantitative analysis method/technique, where the data needs to be calculated using mathematical calculations in Microsoft Excel software. The results of the analysis show that the water demand in Batu Merah Village RT.004/Rw 017, based on the analysis results obtained, is 164.64 m³/day. Meanwhile, the reservoir capacity is not able to accommodate water needs so the water is not enough for the needs of the people of RT 004/ RW 017 Air Besar Batu Merah Village. Water flow is carried out 24 hours per day, because the required discharge based on the calculation results is insufficient for the RT 004/ RW 017 Air Besar Batu Merah Village area. From the calculation results of the discharge requirement: 113.94 m3/day and the population for the next 5 years is: 1002 people with water requirements of: 135.27 m3/day, then the clean water requirement for RT 004/RW 017 is not sufficient for the next 5 years.